HPV vaccination program in schools – the role of primary health care in the implementation of the National Oncology Strategy - Guzanowski, Łukasz (Lekarz POZ, 2025)
To present the role of primary health care (PHC) physicians in implementing the human papillomavirus (HPV) vaccination program in the school environment as part of the National Oncology Strategy for 2020-2030, to present the current status of the program implementation from the perspective of the primary health care, to indicate organizational difficulties, and to formulate practical recommendations. The HPV Vaccination Program has been implemented in Poland since June 1, 2023. To address low vaccination rates in the target group, educational institutions have been included in the program implementation. Since September 1, 2024, vaccinations have been delivered in schools collaborating with local PHC clinics. The program is a part of the National Oncology Strategy for 2020-2030, a comprehensive document defining the systemic directions of the state’s actions in cancer prevention, diagnosis, and treatment. Although the current vaccination coverage is low, the initial months of implementation suggest the school model has great potential. HPV vaccination, as an element of oncological prevention, has proven effective and is widely supported by population data. Its effective implementation in Poland depends on the involvement of primary healthcare and schools, as well as on the systemic organizational and informational support. Properly conducted education, clear communication, and systemic cooperation can translate into increased vaccination coverage.